2014
DOI: 10.1007/s12927-014-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling queues with simulation versus M/M/C models

Abstract: This paper examines the performance of single-queue service systems using a combination of computer simulation and M/M/C queuing models. Our results show that the accuracy of M/M/C models is significantly affected by the assumptions supporting the models. Managers should therefore exercise caution in using the M/M/C models for designing queuing systems when the models' assumptions are violated. Our results show that cost-centric and servicecentric firms should manage their queues differently. While cost-centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Xu and co-workers reported a pioneering work that enzyme-responsive peptide-based precursors could penetrate in cell membranes and self-assemble into nanofibers inside living cells, [83] which could affect cellular functions and further induce cell apoptosis due to the promiscuous interactions between nanofibers and cytoskeletal proteins resulting in the change of cytoplasm. [84] The similar phenomena were also reported by Ulijn, [85] Maruyama, [86] Yang, [87] and Wells. [88]…”
Section: Enzyme-responsive Hydrogelatorssupporting
confidence: 81%
“…Xu and co-workers reported a pioneering work that enzyme-responsive peptide-based precursors could penetrate in cell membranes and self-assemble into nanofibers inside living cells, [83] which could affect cellular functions and further induce cell apoptosis due to the promiscuous interactions between nanofibers and cytoskeletal proteins resulting in the change of cytoplasm. [84] The similar phenomena were also reported by Ulijn, [85] Maruyama, [86] Yang, [87] and Wells. [88]…”
Section: Enzyme-responsive Hydrogelatorssupporting
confidence: 81%
“…48,49 The oxidation then occurs by a layer-by-layer approach. 14,49 In this study, we have shown the formation of a single oxide nucleus, in the observed particles, which grows as the particles are oxidized. The oxidation occurs at the interface, indicating that the copper or oxygen diffuses preferentially instead of creating new oxide nuclei on the surface.…”
Section:  Results and Discussionmentioning
confidence: 50%
“…Assuming that if the algorithm applies three MongoDB the performance analysis will be better. Performance analysis of queuing model (Queuing Model) [22] are used to design the data communications and network theory to the behavior of the attribute system allows us to do with fast analysis, design, evaluation. The incoming data is being processed in the first place in the queue (First in First Out) storage of data in the form.…”
Section: Interface Servers Interlocking Systems For Sharing Informationmentioning
confidence: 99%